Mesenchymal Stem Cell-Derived Exosomes Enhance FGF-1 and SDF-1 Expression in Rats with Second Degree Burns - Nova Putri Hariani; Agung Putra; Prasetyowati Subchan; Eko Setiawan (MCBS (Molecular and Cellular Biomedical Sciences), 2025)
Background: Second-degree burns cause extensive damage to the skin and pose significant health challenges, with current treatments facing limitations such as donor skin shortages and complications. Fibroblast growth factor 1 (FGF-1) and stromal-derived growth factor 1 (SDF-1) are critical for tissue repair. Emerging evidence suggests that mesenchymal stem cell-derived exosomes (E-MSCs) are a promising cell-free therapeutic option for enhancing wound healing through the modulation of FGF-1 and SDF-1. This study investigated the effect of E-MSCs on the expression of FGF-1 and SDF-1 genes in rats with second-degree burns. Materials and methods:  This experimental study used a second-degree burn model in Wistar rats, treated with subcutaneous injections of E-MSCs at doses of 100 µL and 200 µL. Gene expression of FGF-1 and SDF-1 was quantified using qRT-PCR. Histological validation confirmed burn severity, and flow cytometry was used to characterize E-MSCs and exosomes. Results: An increase in FGF-1 and SDF-1 expression was observed in exosome-treated groups compared to the NaCL-treated group. The 200 µL E-MSCs-treated group showed the most significant enhancement in both growth factors, with statistically significant differences (p<0.05). These findings underline the efficacy of E-MSCs in modulating critical genes involved in wound healing. Conclusion: E-MSCs significantly upregulate FGF-1 and SDF-1 expression, promoting tissue repair and regeneration in second-degree burn models. This study highlights the potential of E-MSCs as a non-invasive therapeutic approach. Keywords: exosomes, FGF-1, mesenchymal stem cells, SDF-1